Caries dental en niños de 0-5 años del municipio de Andes, Colombia. Evaluación mediante el sistema internacional de detección y valoración de caries - ICDAS (2017)
ABSTRACT: The lack of information on dental caries limits the actions of the program called “Alliance for a Cavity Free Future” in the Andes municipality, Colombia. Objective: to establish a baseline for dental caries in primary dentition among children aged 0 to 5. Methodology: a total of 623 children were examined in order to detect the presence of dental caries and its severity. This analysis was conducted using the criteria of the International Caries Detection and Assessment System, icdas. In addition, the experience and prevalence ratios were calculated along with the cicdas 5-6, mft and cicdas 1-6 mft indices. Results: 38.2% of the children had experienced severe caries; the percentage of caries experienced increased to 88.4% when initial and moderate dental caries lesions were included. The data showed that 4.9% of the one-yearolds had untreated severe carious lesions, and this percentage increased to 53.6% for five-year-olds. The dICDAS 5-6 mft index was 0.15±0.8 for one-year-olds and 2.79±3.6 for fiveyear-olds, increasing to 1.97±2.9 and 9.61±4.6, respectively when initial and moderate dental caries lesions were included - dicdas 1-6 mft. Discussion: dental caries is present from the first year in 58.8% of children, this is twice the amount reported for Colombia and for the same age (29.3%). Conclusion: the findings highlight the need to design comprehensive strategies for controlling the disease. Such strategies should include oral health in the early policies and programs dealing with early childhood. Key words: dental caries, ICDAS, baseline, epidemiology, oral health, primary teeth.